Tra Vinh University Journal of Science Special Issue (H. Agricultural Publishing, 2024)
Tra Vinh University Journal of Science are grouped into 04 discipline-specific sections, including: Agriculture - Aquaculture ; Culture - Education - Arts ; Economics - Social Sciences ; Technological - Environmental Sciences.
Keywords: Tạp chí